2021
DOI: 10.1098/rsos.210402
|View full text |Cite
|
Sign up to set email alerts
|

Hydroacoustic and hydrodynamic investigation of bio-inspired leading-edge tubercles on marine-ducted thrusters

Abstract: Underwater radiated noise (URN) has a negative impact on the marine acoustic environment where it can disrupt marine creature's basic living functions such as navigation and communication. To control the ambient ocean noise levels due to human activities, international governing bodies such as the International Maritime Organization (IMO) have issued non-mandatory guidelines to address this issue. Under such framework, the hydroacoustic performance of marine vehicles has become a critical factor to be evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…(2021 b , 2022) proposed a fix to this problem. The porous approach was recently pursued by Stark & Shi (2021) and Kimmerl, Mertes & Abdel-Maksoud (2021). In particular, Stark & Shi (2021) analysed the acoustic signature of four-bladed ducted thrusters, using data from improved delayed detached-eddy simulation (IDDES), conducted on an unstructured hexahedral mesh consisting of about 13 million elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021 b , 2022) proposed a fix to this problem. The porous approach was recently pursued by Stark & Shi (2021) and Kimmerl, Mertes & Abdel-Maksoud (2021). In particular, Stark & Shi (2021) analysed the acoustic signature of four-bladed ducted thrusters, using data from improved delayed detached-eddy simulation (IDDES), conducted on an unstructured hexahedral mesh consisting of about 13 million elements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the porous formulation is typically affected by the issue of the spurious sound due to the eddies crossing the permeable surface of integration, although the recent works by Zhou, Wang & Wang (2021a) and Zhou et al (2021bZhou et al ( , 2022 proposed a fix to this problem. The porous approach was recently pursued by Stark & Shi (2021) and Kimmerl, Mertes & Abdel-Maksoud (2021). In particular, Stark & Shi (2021) analysed the acoustic signature of four-bladed ducted thrusters, using data from improved delayed detached-eddy simulation (IDDES), conducted on an unstructured hexahedral mesh consisting of about 13 million elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability is aided by the small bumps or leading-edge (LE) tubercles located on the pectoral fins of the mammal [7]. LE tubercles have been researched on applications such as aero/hydrofoils, tidal turbines, rudders and marine propulsors [8][9][10][11][12][13][14][15][16]. LE tubercles produce counter-rotating vortex pairs which can influence the local flow-field, and the tubercle modifications have shown to alter the cavitation development on a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation showed that cavitation can be contained and URN levels can be reduced in certain operating conditions. More recently, LE tubercles have been applied to open and ducted propellers blades, as well as the duct [12][13][14][15][16]. Using CFD, Stark and Shi [13] showed that tubercle modified marine propellers could enhance hydrodynamic efficiency under heavycavitating conditions while the tubercles induced a cavitating fencing pattern, confining the sheet cavitation to behind the trough regions which resulted in a reduction in cavitation volume.…”
Section: Introductionmentioning
confidence: 99%